Various Themes in Sarojini Naidu’s Poetry - Chouhan, Sandhya (Journal of Advanced Research in English & Education, 2021)
Sarojini Naidu is the most lyrical of the Indian English poet. Because of the sweetness and musicality of hor verse, she was fondly called by Mahatma Gandhi “the nightingale of India.” In the early phase of her poetic corear, she was anamored by British romantic poets and imitated them in her poetry. But on the advice of Edmund Morris, she tried to reveal the heart of India romantically, lyrically and sensuously. Consequently, she published three volumes of the poem: “The Golden Threshold” [1905]. ‘The Bird of Time’ [1912] and ‘The Broken Wing’ [1917]. These volumes were highly praised by the western literary magzines like ‘The Time’, ‘The Glasgow Horald’, ‘The New York Times’ How to cite this article:  Chouhan S. Various Themes in Sarojini Naidu’s Poetry. J Adv Res Eng & Edu 2020; 5(2): 13-14. DOI: https://doi.org/10.24321/2456.4370.202008